Practice patterns to improve pre and post-transplant medication adherence in heart transplant centres: a secondary data analysis of the international BRIGHT study. (1st April 2018) - Senft, Yuliya; Kirsch, Monika; Denhaerynck, Kris; Dobbels, Fabienne; Helmy, Remon; Russell, Cynthia L; Berben, Lut; De Geest, Sabina; ,; Crespo-Leiro, Maria G; Cupples, Sandra; De Simone, Paolo; et al.
Abstract: Background: As medication non-adherence is a major risk factor for poor post-transplant outcomes, we explored how adherence is assessed, enhanced and integrated across the transplant continuum. Aim: The aim of this study was to study practice patterns regarding pre- and post-transplant medication adherence assessment and interventions in international heart transplant centres. Methods: We used data from the Building Research Initiative Group: chronic illness management and adherence in heart transplantation (BRIGHT) study, a cross-sectional study conducted in 36 heart transplant centres in 11 countries. On a 27-item questionnaire, 100 clinicians (range one to five per centre) reported their practice patterns regarding adherence assessment and intervention strategies pre-transplant, immediately post-transplant, less than one year, and one or more year post-transplant. Educational/cognitive, counselling/behavioural and psychosocial/affective strategies were assessed. Clinicians' responses (intervention present vs. absent; or incongruence in reporting intervention) were aggregated at the centre level. Results: The adherence assessment method most commonly used along the transplant continuum was questioning patients (range 75–88.9%). Pre-transplant, all three categories of intervention strategy were applied. Providing reading materials (82.9%) or instructions (68.6%), involving family or support persons in education (91.4%), and establishing partnership (91.4%) were used most frequently. Post-transplant, strategies closely resembled those employed pre-transplant. Training patients (during recovery) and cueing were more often applied during hospitalisation (74.3%). After the first year post-transplant, except for motivational interviewing (25.7–28.6%), the number of strategies decreased. Conclusions: Across the transplant continuum, diverse adherence interventions are implemented; however, post-transplant, the frequency of adherence interventions decreases. Therefore, increased investment is necessary in long-term adherence interventions.